The Effect of Different Types Manure and Altitude on Wheat Production - Siti Nurul Iftitah; Nurul Baroroh Ayyu Rahmawati; Vatjarjinanto Vatjarjinanto; Ringguh Puji Utami (Gontor Agrotech Science Journal, 2023)
The aim of this research is to know the effect of different manure types on the yield of wheat (Triticum aestivum L.) dewata 162 at different altitudes. The study used a factorial experiment arranged in a completely randomized block design with three replications. The first factor is the type of manure; cow, chicken, goat manure. The second factor is the difference in altitude; lowlands, midlands, and highlands. The results showed that the application of manure and different altitudes affected several parameters such as protein content, gluten content, and the weight of 1.000 dry beans. Chicken manure showed the highest dry weight of 1,000 seeds. The highest content of protein, gluten, and weight of 1,000 dry seeds are found in the lowlands.